Difference on Cefoxitin and Oxacillin Disk Test on In Vitro MRSA Detection (Meticillin Resistant Staphylococcus aureus) Experimental Study on Microbiology Laboratorium of Medicine Faculty of UNISSULLA - Mustikawati, Hana Tiyas; Wahyutomo, Ridha; Djaman, Qathrunnada (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2015)
Background: MRSA phenotypic detection has been a problem since it was found in 1962. Some studies explain that the diffusion method of cefoxitinand oxacilin disk test can be used to detect MRSA. Objective: knowing if there is difference between cefoxitin disk test and oxacilin disk test to detectMRSA.Method: laboratory experimental research with diagnostic test design. Research was done at the laboratory of medicine faculty of UNISSULA using 24 watch glasses, 12 with MRSA bacteria (Meticillin Resisten Staphylococcus aureus), and the other 12 with MSSA bacteria (Meticillin sensitive Staphylococcus aureus). specimentsThe results were classified into sensitive and resistant category based on CLSI standard (Clinical Laboratory Standards Institute).Hypothesis test using fisher test, with significance level <0,05Results: speciments MRSA detection using cefoxitin disk resulted 12 resistant speciments and no sensitive speciments. The oxacilin disk resulted 9 resistant speciments and 3 sensitive speciments. MSSA detection using cefoxitin disk resulted no resistant speciments and 12 sensitive speciments, oxacilin disk resulted no resistant speciments and 12 sensitive speciments. Diagnostic test was done by CEBM statistic calculator. The sensitivity and specificity value of MRSA sampels using cefoxitin disk were 96,2% & 96,2%, PPV (positive predictive value) 96,2%, NPV (negative predictive value) with was 96,2%. While the oxacilin disk, the sensitivity was 73,1%, specificity 96,2%, PPV 95,0%, NPV 73,8%. The result of fisher test for cefoxitin disk and oxacilin disk was p=0.000 meant there was difference between cefoxitin disk test and oxacilin disk test to detect MRSA.Conclusion: diffusion method in cefoxitin disk is better than oxacillin disk in MRSA detection.